Eschatological Notions in Post-Socialist Bulgaria - Evgenia Troeva (Yearbook of Balkan and Baltic Studies, 2022)
The text presents the most popular ideas about the end of the world that spread in Bulgaria in the post-socialist period. In the years of transition after 1989, social and political changes, as well as an economic crisis, favoured apocalyptic expectations. In contrast to the past, when the religious explanation of the world’s end dominated, in contemporary times the apocalypse is more frequently related to cosmic and natural disasters or to the negative effects of human activity. A characteristic view of the end of the world is imagining it as a new beginning. In the present, there is also a transformation in the mechanism for shaping ideas about the end of the world. Modernization, globalization, and new technologies are changing both people’s daily lives and their ideas about the fate of the human world. After the boom of apocalyptic expectations in Bulgarian society at the end of the twentieth century and the beginning of the twenty-first century, in recent years we have seen a rationalization of the eschatological notions and their close connection with ecological and political arguments.